RELIEF PHYSICAL FEATURES SCREENING OF GUARAPUAVA-PR THROUGH GEOPROCESSING TECHNIQUES - Andrey Luis BINDA; Luiz Gilberto BERTOTTI (Revista Raega: O Espaço Geográfico em Análise, 2008)
The relief is the main physical agent that interferes with human occupation. Normally, occupation begins in favorable areas and only later, with the urban expansion, it extends to unfavorable ones. In this context, this work aims to elaborate an integrated study of the relief physical features of Guarapuava-PR urban perimeter. Three methodological procedures were used: bibliographic research, field and laboratory/cabinet works. Screening of several variables (hydrography and urban river basin, hipsometry, declivity, source exposition, relief soil and shape) was performed through geoprocessing techniques using SPRING version 4.3.3 software. The knowledge of urban space physical features, limitations and potentialities is important to establish more reasonable actions regarding soil usage and to make urban planning that fits better such specifity.